Posttraumatic Growth in Adolescent Survivors of the Mount Merapi Eruption Disaster - Muslihaturrobiah, Muslihaturrobiah; Triyono, Triyono (Jurnal Psikologi Teori dan Terapan, 2025)
Background: Natural disasters can cause material losses and psychological trauma, but on the other hand, it has the potential to trigger positive impacts such as post-traumatic growth (PTG). Therefore, this study will specifically examine PTG in adolescent survivors of the Mount Merapi eruption in Balerante Village, Kemalang, Central Java. Objective: Exploring more deeply about PTG (Post-Traumatic Growth) in adolescent survivors of the Merapi volcanic eruption in Balerante Village. Method: A qualitative phenomenological approach involving four subjects aged 19-24 years who directly experienced the Mount Merapi eruption disaster. Informants were selected using the snowball sampling technique. Data collection was conducted through observation and in-depth interviews. The data analysis technique employed was Interpretative Phenomenological Analysis (IPA). Result: The results showed that PTG in adolescent survivors of the Mount Merapi eruption was reflected in disaster preparedness, positive post-traumatic changes, and the emergence of new ambitions. Factors contributing to PTG included social support and individual spirituality. Conclusion: Trauma can be a turning point for adolescents, allowing them to grow into more resilient individuals in living their lives.   Keywords: Adolescents; mount Merapi eruption disaster; posttraumatic growth.   Abstrak Latar Belakang: Bencana alam dapat menyebabkan kerugian materi, dan trauma psikologis, namun juga berpotensi memicu dampak positif seperti posttraumatic growth (PTG). Meski penelitian PTG pada penyintas bencana alam sudah banyak dilakukan, kajian spesifik tentang PTG pada remaja penyintas erupsi Gunung Merapi di Desa Balerante, Kemalang, Jawa Tengah, belum tersedia. Tujuan: Mengeksplorasi lebih mendalam mengenai PTG pada remaja penyintas bencana erupsi Gunung Merapi di Desa Balerante. Metode: Kualitatif fenomenologi yang melibatkan empat subjek berusia 19-24 tahun yang mengalami langsung bencana Erupsi Gunung Merapi. Informan dipilih melalui teknik snowball sampling. Pengambilan data menggunakan observasi dan wawancara mendalam. Teknik analisis data yang digunakan yaitu Interpretative Phenomenological Analysis (IPA). Hasil: Hasil penelitian ini menunjukkan PTG pada remaja penyintas bencana erupsi Merapi ditunjukkan dalam bentuk kesiagaan menghadapi bencana, perubahan positif setelah trauma, dan munculnya ambisi baru. Faktor pendorong yang mempengaruhi PTG diantaranya dukungan sosial dan spiritualitas pada masing-masing individu. Penelitian ini diharapkan dapat mendukung intervensi psikologis dan program penguatan potensi PTG. Simpulan: Trauma dapat menjadi titik balik bagi remaja untuk tumbuh menjadi individu yang lebih tangguh.dalam menjalani kehidupan.   Kata Kunci: Bencana erupsi gunung Merapi; posttraumatic growth; remaja.